2021
DOI: 10.1007/s00603-021-02647-0
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Uniaxial Compressive Strength of a Limestone Exposed to High Temperatures by Point Load and Leeb Rebound Hardness Testing

Abstract: The effect of exposure to high temperature on rock strength is a topic of interest in many engineering fields. In general, rock strength is known to decrease as temperature increases. The most common test used to evaluate the rock strength is the uniaxial compressive strength test (UCS). It can only be carried out in laboratory and presents some limitations in terms of the number, type and preparation of the samples. Such constrains are more evident in case of rocks from historical monuments affected by a fire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…Point load strength is a simple, fast and inexpensive index test method that can be applied both in the field and in the laboratory. To determine this strength, core samples (for diametric and axial tests), cut block samples or irregular-sized samples can be used [35,36]. In this study, cut block samples were preferred.…”
Section: Point Load Strength Testmentioning
confidence: 99%
“…Point load strength is a simple, fast and inexpensive index test method that can be applied both in the field and in the laboratory. To determine this strength, core samples (for diametric and axial tests), cut block samples or irregular-sized samples can be used [35,36]. In this study, cut block samples were preferred.…”
Section: Point Load Strength Testmentioning
confidence: 99%
“…The thermal fatigue effects of rock have been considered as an important factor that can evidently affect the physical–mechanical behaviors of rocks like its microstructure, strength, and deformation instability process 1–5 . The thermal fatigue damage induced by high temperature will induce the change of internal structure of rocks, 6,7 resulting in the destructive instability of rock mass in some geotechnical engineering applications such as enhanced geothermal system, nuclear waste storge, deep mining, rock drilling, and rock engineering exposed to fire or explosion 8–12 . Currently, the thermal fatigue damage of rock has become a design factor that cannot be ignored in rock engineering under high‐temperature environment 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…As a hot research topic, the thermal fatigue effects of rock have been widely studied, which primarily concentrated on the physical properties and mechanical behaviors for different types of rocks, such as P‐wave velocity, 15,16 permeability, 17–19 density, 20,21 mineral characteristics, 22,23 porosity, 18,24 elastic modulus, 25,26 tensile strength, 21,27 compressive strength, 12,28 fracture toughness, 5,8,29 and fracture behaviors 30–33 . For example, Rong et al 15 revealed the evolution behaviors of P‐wave velocity for bedrocks subjected to thermal cycling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rock mass strength is one of the most important mechanical properties of rock (Garrido et al, 2022), which is affected by particle arrangement, discontinuity, saturation, temperature, humidity, and/or weathering (Ji and Arson, 2020). Determining the rock mass strength and deformation is a key field of rock mechanics (Walton, 2019).…”
mentioning
confidence: 99%